Association between periodontitis and gastrointestinal cancer risk and prognosis: evidence from a nested case–control study in Southwest China - Luo, Ting; Li, Juan; Pu, Ke; Yang, Guodong (European journal of medical research, 2025)
With low early detection rates and high incidence and mortality, Gastrointestinal cancer (GIC) imposes a significant global health burden. Emerging evidence indicates that periodontitis may be a potential risk factor for GIC development; however, epidemiological data remains inconclusive. This study aimed to examine the impact of periodontitis on the incidence, recurrence, and metastasis of GIC in Southwest China, thereby offering epidemiological evidence to support GIC prevention and management. Between September 2022 and August 2024, a case-control study was conducted at the Affiliated Hospital of North Sichuan Medical College. Five hundred GIC patients were included as the case group based on the predefined inclusion and exclusion criteria, while 1005 healthy individuals were recruited for the control group. Multivariate analyses were performed to examine the associations between periodontitis and GIC incidence, recurrence, and metastasis while controlling for potential confounding factors. The results of this study demonstrated that periodontitis was significantly associated with the incidence of esophageal, gastric, and colorectal cancer. Even after adjusting for potential confounders, it remained a significant risk factor for esophageal cancer (OR = 2.810, 95% CI 1.032-7.649, P = 0.043), colon cancer (OR = 2.330, 95% CI 1.072-5.067, P = 0.033), and rectal cancer (OR = 2.730, 95% CI 1.247-5.379, P = 0.012). Compared to non-periodontitis subjects, periodontitis showed a significant association with distant metastasis of rectal cancer (aHR = 5.332, 95% CI 1.406-20.220, P = 0.014). Moreover, severe periodontitis was identified as an risk factor for distant metastasis in rectal cancer (aHR = 10.138, 95% CI 1.824-56.354, P = 0.008). This study highlights significant associations between periodontitis and an increased risk of esophageal and colorectal cancers. Additionally, patients with rectal cancer and periodontitis exhibited an increased risk of distant metastasis compared to those without periodontitis.